Preventing cultural displacement in multicultural societies as reflected in Persimmons by Li-Young Lee - Oxa Ardyan Fathurozi; Rahayu Puji Haryanti (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This study explores the portrayal of cultural displacement and efforts to preserve cultural identity in Li-Young Lee’s poem Persimmons using Michael Riffaterre’s Semiotics of Poetry. Cultural displacement—caused by language barriers, institutional isolation, and cultural misrepresentation—poses serious risks to identity continuity in multicultural societies. The poem serves as a powerful literary example of how immigrant experiences reflect both trauma and resistance. Using qualitative textual analysis, this study applies Riffaterre’s concept of matrix, model, variants, hypogram, and textual interpretants to uncover how the poem conceals deeper cultural meanings beneath language conflict and metaphor. Findings reveal that Persimmons portrays cultural displacement through linguistic confusion, memory loss, and institutional punishment, symbolized by the misinterpretation of the persimmon fruit. However, the poem also emphasizes the preservation of cultural identity through sensory memory, family traditions, and symbolic reclamation. The persimmon functions as a hypogram—a hidden sign of heritage—representing emotional and cultural continuity. This research contributes to literary semiotics and postcolonial discourse by demonstrating how poetic language can resist cultural erasure and affirm identity within multicultural contexts. Ultimately, the study shows that the poetry like Persimmons serves not only as a personal expression but as a powerful mode of cultural preservation and resilience.